Business graduate-ness and work-readiness: a comparative analysis of public and private universities in Bangladesh / Hasina Akter - Akter, Hasina (Universiti Teknologi MARA, 2020)
Quality education is a crucial component of human capital, which has emerged large in the theories explaining economic growth, in particular, and the development discourse, in general. However, in the new era of business today business studies are prime choices of most of the students, and accordingly, this study focuses merely on the quality of business education. This study compares public and private universities in terms of their efficacy in offering business education focusing on five major factors, namely developing business professionalism, updated curriculum, practical orientation, creating entrepreneurial ability and mindset, employability of business graduates. Data used in this study is primary as well as secondary. Primary data have collected from 600 respondents – 300 from each category of universities. Different statistical tools, such as Chi-square test and two sample t-test, have been applied for analysing the data. Findings reveal that private universities slightly better perform in terms of developing business professionalism, updated curriculum, and creating entrepreneurial mindset. However, what most importantly matter are practical orientation and employability, in which public universities are more prompt compared to their private counterparts.